Novel imidazo[1, 5-a]quinoxaline derivatives: SAR, selectivity and modeling challenges en route to the identification of an α5-GABAA receptor NAM. (15th January 2023) - Károlyi, Benedek Imre; Potor, Attila; Kapus, Gábor László; Fodor, László; Bobok, Amrita; Krámos, Balázs; Magdó, Ildikó; Bata, Imre; Szabó, György
Graphical abstract: Abstract: Initial optimization of a series of novel imidazo[1, 5- a ]quinoxaline compounds originated from a heuristic approach combining two known structural moieties towards α5-GABAA receptor is shown. This work reveals one-digit nanomolar active compounds as well as positive and negative allosteric modulators resulted from our exploratory approach. To deepen our understanding, their diverse mechanistic nature resulted from in silico modeling is also disclosed.